A Model of Teaching Metacognition in Solving Mathematical Word Problems - Reyes, Joseph D.; Reyes, Zenaida Q. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This qualitative study aimed to propose a model for teaching metacognition in solving mathematical word problems, utilizing a Multiple Case Study Method. The research explored how teachers employ metacognitive strategies, focusing on two components: knowledge of cognition and regulation of cognition. The findings suggest that metacognitive instructional techniques enhance students' mathematical knowledge and problem-solving abilities. Teachers who incorporate various metacognitive strategies help students develop their own learning skills and create conditions for meaningful learning. The study concludes that connecting metacognitive teaching approaches makes math problem-solving more significant. The proposed model allows teachers flexibility in applying strategies based on their circumstances and students' needs. Importantly, the research emphasizes that mathematics teachers must have a thorough understanding of mathematical concepts to effectively implement metacognitive methods.